Jane on her own - Le Guin, Ursula K.; Schindler, S. D. (Ochard Books New York, 2006)
Jane on Her Own by Ursula K. Le Guin is a children's fantasy novel, part of the Catwings series. The story follows Jane, a young cat with wings, as she embarks on an adventure away from her family to explore the world on her own. Along the way, Jane faces challenges, learns about independence, and discovers the importance of courage and self-reliance. Through Jane's journey, the book explores themes of growing up, facing fears, and finding one's place in the world. Le Guin's gentle prose and imaginative storytelling make it a heartwarming read for young audiences.